Sovereign Debt, the Blessing Aspects and the Implications for the Euro Area - Gabriella Chiesa (Vierteljahrshefte zur Wirtschaftsforschung, 2020)
The Euro area has a unique monetary authority that governs money creation, but several individual countries' sovereign debts that differ in terms of safety. We analyse: i) the interactions between the financial and real sector in such an environment; ii) the role of government bonds as liquidity instruments; iii) whether and how the correlation structure of the sovereign-bonds' market values affects the portfolio composition of liquidity instruments and prices, and the scope for a debt management policy at the Euro area level. – – Der Euroraum hat eine einheitliche Währungsbehörde, die die Geldschöpfung regelt, aber die einzelnen Eurostaaten begeben jeweils ihre eigenen Staatschulden. Folglich ist auch die Sicherheit der Staatsanleihen sehr unterschiedlich. Vor diesem Hintergrund wird analysiert: i) die Wechselwirkungen zwischen dem finanziellen und dem realer Sektor; ii) die Rolle von Staatsanleihen als Liquiditätsinstrumente; iii) ob und wie sich die Korrelation der Marktwerte der Staatsanleihen auf die Zusammensetzung von liquiden Instrumenten im Portfolio und die Preise derselben auswirkt und den Spielraum für eine Schuldenmanagementpolitik im Euroraum einschränkt.
Keywords: E44; H63; G18; 330; Safe assets; liquidity; sovereign debt management; sovereign debt spreads